2017
DOI: 10.1037/edu0000154
|View full text |Cite
|
Sign up to set email alerts
|

The importance of additive reasoning in children’s mathematical achievement: A longitudinal study.

Abstract: This longitudinal study examines the relative importance of counting ability, additive reasoning, and working memory in children's mathematical achievement (calculation and story problem solving). One hundred and fifteen 6-year-old Chinese children in Hong Kong participated in two waves of assessments (T1-first grade and T2-second grade). Multiple regression analyses showed that counting ability explained a significant amount of variance in T1 and T2 calculation beyond the effects of age, IQ, and working memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 113 publications
1
24
0
5
Order By: Relevance
“…Yet the relation between mathematical symbol understanding and mathematical competence has seldom been investigated—until recently, when researchers obtained promising results. For instance, in one study, children's understanding of commutativity and inversion predicted their growth in mathematical competence across 1 year (Ching & Nunes, 2017). Likewise, another study observed similar predictions based on children's understanding of equivalence (McNeil et al, 2019).…”
Section: Understanding Mathematical Symbols and Their Relevant Princimentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the relation between mathematical symbol understanding and mathematical competence has seldom been investigated—until recently, when researchers obtained promising results. For instance, in one study, children's understanding of commutativity and inversion predicted their growth in mathematical competence across 1 year (Ching & Nunes, 2017). Likewise, another study observed similar predictions based on children's understanding of equivalence (McNeil et al, 2019).…”
Section: Understanding Mathematical Symbols and Their Relevant Princimentioning
confidence: 99%
“…Fortunately, the correlation between mathematical symbol understanding and mathematical competence has captured researchers’ attention in recent years (Ching & Nunes, 2017; McNeil et al, 2019). Furthermore, new measures developed to assess the ability to identify the schema behind mathematical problems (Wong & Ho, 2017; Yip et al, 2020) have allowed more detailed investigations into situation comprehension and mathematization.…”
Section: The Next Step: Examining the Unique Roles Of The Three Compomentioning
confidence: 99%
See 1 more Smart Citation
“…The commutative principle (part a + part b = part b + part a)-that is, the irrelevant order of the addends-is one of the essential properties of the part-whole relationship of numbers (Kilpatrick et al, 2001). In addition to facilitating learners' computational fluency, the commutative principle is integral to part-whole reasoning (Ching & Nunes, 2017) such as understanding that the relation among three quantities, for example 5/4/1, can be expressed with symbols (e.g., 1 + 4 = 5; 4 + 1 = 5) and that both equations describe the same part-whole relation. Previous research has shown that children acquire informal knowledge of commutativity before entering school.…”
Section: Mathematical Principles Linked To Part-whole Relationshipsmentioning
confidence: 99%
“…It is critical that children enter kindergarten and first grade prepared to embark on formal math learning, however, there is wide variation in the level of math skill children acquire during the preschool years (Jordan et al, 2006 ). Conceptual knowledge of addition and subtraction is an especially important skill for children at the beginning of formal math education (Nunes et al, 2007 ; Ching and Nunes, 2017 ). Therefore, improving early conceptual knowledge of arithmetic is an important way to enhance math readiness in preschool children.…”
Section: Introductionmentioning
confidence: 99%